2021
DOI: 10.1039/d0sc05725h
|View full text |Cite
|
Sign up to set email alerts
|

Regiodivergent synthesis of pyrazino-indolines vs. triazocines via α-imino carbenes addition to imidazolidines

Abstract: Hexahydropyrazinoindoles were prepared in a single step from N-sulfonyl triazoles and imidazolidines. Under dirhodium catalysis, α-imino carbenes were generated and formed nitrogen ylide intermediates that, after subsequent aminal opening, afforded...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 88 publications
0
18
0
Order By: Relevance
“…First, the nature of the metal catalyst was investigated, 2 switching from copper to dirhodium and cyclopentadienyl ruthenium complexes ( entries 3 and 4 ) while decreasing the temperature to 60 °C with these more reactive decomposition catalysts. Using Rh 2 (OAc) 4 (1 mol‐%), [45] a yield of 37 % was obtained, while decomposition with [CpRu(MeCN)] 3 PF 6 (2.5 mol‐%) [46,47] led to a drastic improvement and a corresponding yield of 80 %. Selecting the [CpRu] complex for further experiments, the influence of the negative counterion was investigated, switching from PF 6 − to the large, lipophilic and less coordinating BAr F − anion [42] .…”
Section: Resultsmentioning
confidence: 99%
“…First, the nature of the metal catalyst was investigated, 2 switching from copper to dirhodium and cyclopentadienyl ruthenium complexes ( entries 3 and 4 ) while decreasing the temperature to 60 °C with these more reactive decomposition catalysts. Using Rh 2 (OAc) 4 (1 mol‐%), [45] a yield of 37 % was obtained, while decomposition with [CpRu(MeCN)] 3 PF 6 (2.5 mol‐%) [46,47] led to a drastic improvement and a corresponding yield of 80 %. Selecting the [CpRu] complex for further experiments, the influence of the negative counterion was investigated, switching from PF 6 − to the large, lipophilic and less coordinating BAr F − anion [42] .…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the same group reported the single-step preparation of hexahydropyrazinoindoles 92.3 through a Rh­(II)-catalyzed cascade reaction of N -sulfonyl-1,2,3-triazoles 92.1 and imidazolidines 92.2 (Scheme ). This cascade also involves sequential carbene generation, ylide formation, [1,2]-Stevens, and Friedel–Crafts reactions. Interestingly, treatment of triazoles 92.6 with unsymmetrical imidazolidines 92.7 led to the unprecedented formation of eight-membered hexahydro-1,3,6-triazocines 92.8 , in contrast to the symmetrical imidazolidines.…”
Section: Denitrogenative Transformations Of Triazolesmentioning
confidence: 99%
“…Guinchard et al also reported an Au(I)-catalyzed Pictet–Spengler reaction to prepare a variety of complex heterocyclic compounds including tetrahydro-pyrazinoindoles with good yields ranging from 43 to 93% [ 21 ]. In 2021, Lacour et al reported that N -sulfonyltriazoles 26 and imidazolines 27 reacted under rhodium catalysis to give a variety of hexahydro-pyrazinoindoles 28 with excellent yields easily transformed in tetrahydropyrazinoindoles 29 after a welcome rearrangement in triflic acid TfOH [ 22 ]. Ghorai et al reported in 2018 of an elegant synthesis of 1,3-disubstituted 1,2,3,4-tetrahydropyrazino[1,2- a ]indoles 32 with excellent stereoselectivity (de, ee >99%) via base-mediated ring opening of chiral aziridines 31 with skatoles 30 followed by BF 3 -OEt 2 catalyzed Pictet–Spengler reaction [ 23 ].…”
Section: Pyrazinoindoles A: Synthesis and Biological Propertiesmentioning
confidence: 99%